2020
DOI: 10.1109/access.2020.3012812
|View full text |Cite
|
Sign up to set email alerts
|

Link Between Sustainability and Industry 4.0: Trends, Challenges and New Perspectives

Abstract: The increasing number of studies that underline the relationship between industry 4.0 and sustainability shows that sustainability is one of the pillars of smart factories. Through a bibliometric performance and network analysis (BPNA), this research describes the existing relationship between industry 4.0 and sustainability, the strategic themes from 2010 to March 2019, as well as the research gaps for proposing future work. With this goal in mind, 894 documents and 5621 keywords were included for bibliometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(122 citation statements)
references
References 191 publications
(273 reference statements)
4
89
0
7
Order By: Relevance
“…The results presented are in line with other similar studies [17]- [21], while the critical discourse on the challenges revealed additional insights and directions. These challenges are mainly based on the fact that digitized and adequately modelled data/information is at the disposal for being analyzed and used to support all functions associated with the different phases of the life cycle of the physical and cyber-part of a RAMI 4.0-compliant solutions.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The results presented are in line with other similar studies [17]- [21], while the critical discourse on the challenges revealed additional insights and directions. These challenges are mainly based on the fact that digitized and adequately modelled data/information is at the disposal for being analyzed and used to support all functions associated with the different phases of the life cycle of the physical and cyber-part of a RAMI 4.0-compliant solutions.…”
Section: Resultssupporting
confidence: 90%
“…Table 1 summarizes some of the most critical issues to implement Industry 4.0 and points out the main actions required to address each one of these challenges. The findings below are in line with similar systematic literature reviews [17], [19]- [21].…”
Section: Future Challengessupporting
confidence: 91%
See 3 more Smart Citations